Problems in the education of the patient with allergic rhinitis - Czerwińska Pawluk, Iwona; Szymaszek, Angelo; Pawluk, Elwira Paula; Zukow, Walery (Journal of Education, Health and Sport, 2018)
Allergic rhinitis (AR) due to the complex pathogenesis and steady increase in the incidence of the disease in both children and adults, is a serious problem in modern medicine. The disease affects the quality of life of the patient and / or caregivers. The nurse / nurse plays a leading role in the care of patients with AR, participating in the process of diagnosis, therapy and prevention of disease. Standard in patient care with AR education is intended to prepare the patient for self-control disease.